Prolonged infection by Fonsecaea pedrosoi after antigenic co-stimulation at different sites in experimental murine chromoblastomycosis - Machado, Alexandre Paulo (Landes Bioscience, 2010)
In the present study, we examined prolonged infection after antigenic co-stimulation by inoculation of the fungus Fonsecaea pedrosoi at two different sites in three mouse strains (BALB/c, Swiss and C57BL/6). Using this murine model of infection, we showed that antigen induction of infection at more than one site led to a local suppression of active lesions, which increased the time course of experimental chromoblastomycosis (CBM). Footpad infection with a simultaneous infection of the peritoneum or a mucosal site appeared to cause prolonged infection and frequent fungal disseminations. Using knockout (KO) mice, we observed that antigenic co-stimulation caused progressive illness in CD8-KO animals and an effective immune response in the absence of IL-10. In Xid mice, co-stimulation provoked chronic infection (not prolonged), suggesting that B1 B cells play an important role in the control of fungal infection. The tissue response to infection was similar in all co-stimulated mouse groups, as anatomopathologic sections revealed multifocal lesions (granuloma-like). In general, these mice had acute responses at primary antigenic sites with an intense migration of polymorphonuclear leukocytes (PMNs), whereas the distant infection sites (footpad) showed signs of chronic infection. The migration of PMNs to the secondary site (footpad) increased in the later periods of infection, especially after the disappearance of the primary antigenic focus. PMN migration was associated with lesion-dormancy breakage and fungal elimination. Our findings suggest that the host inflammatory/suppression mechanisms induced by antigenic co-stimulation to systemically fight the same pathogen act coordinately through responses that differ at the sites of infection between acute and chronic integrated healing processes that are more prolonged than an acute infection at a single site. However, the long persistence of fungal cells in the host may be linked to microbial adaptation to a parasitic infection as observed in co-stimulated Xid mice.